IMPREGNASI EKSTRAK JATI DAN RESIN PADA KAYU JATI CEPAT TUMBUH DAN KARET - Efrida Basri; Jamal Balfas (BRIN Publishing, 2014)
Previous research findings have shown that the fast grown teak (JCT) has lower physical, mechanical and durability performances than those of the traditional teak. Hence, a specific effort is required to increase the JCTquality. This research is aimed to improve the quality of JCT and rubber wood through impregnation of extracts and resin.This study used extracts from traditional teak wood sawdust dissolved in methanol solution. The teak extractive solutions were then impregnated into wood structure of JCT and rubber wood with various solution concentrations according to additional organic resin. The organic resins used in this study consist of shellac and damar, which were added at three weight concentration levels of 4, 6 and 8% of the extract volume. The results show that the impregnation of extractive solution into JCT and rubber wood increased dimentional stability of both woods with Anti Shrink Efficiency (ASE) value exceeds 50%, compared to the traditional teak. The addition of shellac and damar resin in the teak extractive solution significantly result in better dimensional stability of both treated woods proportionally in accordance to the resin concentration.